Alternative σI/anti-σI factors represent a unique form of bacterial σ/anti-σ complex. Issue 11 (20th May 2019) - Wei, Zhen; Chen, Chao; Liu, Ya-Jun; Dong, Sheng; Li, Jie; Qi, Kuan; Liu, Shiyue; Ding, Xiaoke; Ortiz de Ora, Lizett; Muñoz-Gutiérrez, Iván; Li, Yifei; Yao, Hongwei; et al.
Abstract: The σ 70 family alternative σ I factors and their cognate anti-σ I factors are widespread in Clostridia and Bacilli and play a role in heat stress response, virulence, and polysaccharide sensing. Multiple σ I /anti-σ I factors exist in some lignocellulolytic clostridial species, specifically for regulation of components of a multienzyme complex, termed the cellulosome. The σ I and anti-σ I factors are unique, because the C-terminal domain of σ I (SigIC ) and the N-terminal inhibitory domain of anti-σ I (RsgIN ) lack homology to known proteins. Here, we report structure and interaction studies of a pair of σ I and anti-σ I factors, SigI1 and RsgI1, from the cellulosome-producing bacterium, Clostridium thermocellum . In contrast to other known anti-σ factors that have N-terminal helical structures, RsgIN has a β-barrel structure. Unlike other anti-σ factors that bind both σ2 and σ4 domains of the σ factors, RsgIN binds SigIC specifically. Structural analysis showed that SigIC contains a positively charged surface region that recognizes the promoter –35 region, and the synergistic interactions among multiple interfacial residues result in the specificity displayed by different σ I /anti-σ I pairs. We suggest that the σ I /anti-σ I factors represent a distinctive mode of σ/anti-σ complex formation, which provides the structural basis for understanding the molecular mechanism of the intricate σ I /anti-σ I system.